Data on molecular docking simulations of quaternary complexes 'Bst exo- polymerase-DNA-dCTP-metal cations' - Garafutdinov, Ravil R. (Data Brief, 2020)
This article reports data related to the research article entitled “Effect of metal ions on isothermal amplification with Bst exo- DNA polymerase” (R.R. Garafutdinov, A.R. Gilvanov, O.Y. Kupova, A.R. Sakhabutdinova, 2020) [1]. Here, the results of molecular simulations of the complexes of Bst exo- DNA polymerase with dCTP triphosphate, double-stranded DNA and divalent metal cations are presented. Energetic parameters, number and type of chemical bonds formed by dCTP with the environment are given.